SISTEM INFORMASI GEOGRAFIS PEMETAAN DAN PENGELOLAAN BANK SAMPAH BERBASIS WEB: SISTEM INFORMASI GEOGRAFIS PEMETAAN DAN PENGELOLAAN BANK SAMPAH BERBASIS WEB - Ratnawati; Rohayati Arifin; Sri Rezki; Ida, Nuraida_Latif (JURNAL ILMU KOMPUTER, 2023)
Currently the existence of waste banks is not fully known by the public. Even though the community knows the existence of a waste bank, the location of the waste bank is very far from its location. In addition, data management for waste banks generally still uses the manual method by only using records in books and not yet utilizing information technology. This study aims to create a Web-Based Geographic and Waste Bank Management System that makes it easier for the waste bank to manage the incoming waste from customers and makes it easier for the public to find the location of the nearest waste bank from their location. The method used in this research is the RAD (Rapid Application Development) method. Research data obtained through field research, literature study. The results of this study are in the form of an information system that can be accessed by users (customers) to find the location of the nearest waste bank from its location, as well as a system that can manage waste storage data in each unit waste bank.